The Use of Voicespice Platform to Improve Speaking Skills - Bastian, Arif Alexander; Karnedi, Karnedi (English Education and Literature Journal (E-Jou), 2026)
Speaking proficiency remains a challenge for non-English major students, particularly those in Informatics Engineering programs, due to limited opportunities for meaningful oral practice in English classes. To address this issue, the research aims to examine the effectiveness of voicespice to be a digital media platform for improving students’ speaking skills. Employing a quasi-experimental design, the study involved 25 Informatics Engineering students at Universitas Aisyah Pringsewu, with pre - test and post - test assessments used to analyze variations in speaking proficiency subsequent to the intervention. The collected data were analyzed using a paired samples t-test. The findings reveal a statistically significant improvement in students’ speaking skills, with a mean gain of 22.52 points (p < 0.05). These results indicate that integrating Voicespice into English instruction provides a practical and innovative approach to enhancing speaking practice, promoting learner autonomy, and increasing students’ confidence in English. This research contributes to the increasing body of scholarship in technology-assisted language learning by highlighting the potential of audio-based platforms in supporting speaking development among non-English major students.